Recommendations for Preparing for Military Action Based on the Analysis of Armed Conflicts in Urban Settings - Комилов Маъруфхон Собирхонович (International Journal of Scientific Trends, 2024)
The ongoing socio-demographic processes in the modern world determine a high probability, and the features of modern military conflicts confirm the facts that modern military operations are mainly carried out in populated areas. Therefore, in order to develop the theory of organizing armed struggle in such conditions, we carried out an analysis, based on the results of which, the article presents practical recommendations for organizing armed struggle in populated areas.